CdSe nanoparticles grown with different chelates - Bacherikov, Yu.Yu.; Davydenko, M.O.; Dmytruk, A.M.; Dmitruk, I.M.; Lytvyn, P.M.; Prokopenko, I.V.; Romanyuk, V.R. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Modified reverse micelles method allowing fabrication of CdSe nanoparticles in toluene solution in series of sizes with average diameter from 1.2 to 3.2 nm and size distribution ∼ 12-30 % is presented. Simple empirical relation between the CdSe nanoparticle diameter and exciton absorption wavelength is proposed, which allows to do prompt and effective monitoring the particles size and size distribution during the synthesis. Optical absorption and photoluminescence measurements as well as EDX demonstrated good quality of obtained nanocrystallites. Besides, study of nanoparticles produced using two complexing agents (SNTA and Trilon B) revealed similar stoichiometric and optical properties. Trilon B is suitable for CdSe nanoparticles growth instead of SNTA. Because of higher stability of the chelate complex of Trilon B and Cd²⁺ ions, it is possible to use higher temperature for growth which allows preparation of large size nanocrystals.